TANGGUNG JAWAB DIREKTORAT JENDERAL HAK KEKAYAAN INTELEKTUAL TERHADAP PEMEGANG HAK ATAS MEREK DALAM HAL ADA PUTUSAN PEMBATALAN MEREK - Hertanti Pindayani (Authentica, 2018)
Many cases of trademark disputes that occur due to the use of brands by parties who are not actually entitled to a trademark, even though the party has a certificate issued by the DG IPR. Therefore, it is necessary to know the responsibility of the Directorate General of Intellectual Property Rights in the event of a decision to cancel trademark registration and to know the criteria used by the Director General of Intellectual Property Rights in providing protection against Trade-mark Rights. This legal issue will be discussed through legal research with a conceptual approach and legislative approach and then analyzed qualitatively. In common, Ditjen HKI often issues certificates of trademark rights, even though the trademarks have already been registered before.  Therefore, they are double owners of similar trademarks. The professionalism of Ditjen HKI officers does not support the implementation of preventing people from breaking the trademark laws. The elements of methods and working techniques of Ditjen HKI officers have not been sufficient in satisfying their customers when they register their trademarks since there has been no computerized information and data management.Keywords: trademark, certificate, violation, trademark cancellation